Efektivitas Rekreasi Bernyanyi Terhadap Peningkatan Activity Daily Living Pada Lansia di Panti Sosial Tresna Werdha Puspakarma Mataram - Achmalona, Teguh; Sutomo, Suswinda Yuli; Wiguna, Reza Indra (Jurnal Kesehatan Qamarul Huda, 2020)
Aging can not be prevented but it can be slowed, aging is not a disease but it is the last phase of kehidupan.Pandangan for the elderly who are weak and sickly causes their activity is restricted resulting in decreased ability of activity. This study aims to determine the effectiveness of recreational singing to the increased activities of daily living in the elderly in Social Institutions Tresna Werdha Puspakarma Mataram. Elderly sampled in this study were elderly people who helped his Daily Living Activity in part, the number of samples used are 10 people with purposive approach sampling.Instrument used are observation and interview guides. The study design used is a pre-experiment with the approach of one group pretest-posttest design and the data were analyzed by t-test statistical tests. Results of the study before recreation showed 10 respondents, eight respondents (80%) experienced a mild degree of dependence ADL and 2 respondents (20%) experienced a moderate level of dependence ADL. After singing recreation do 10 respnden (100%) had mild dependence level, 0 respondents (0%) experienced a moderate level of dependence. The results of this study indicate that recreational singing has a significant effect on the increase daily activity expected next lansia.Untuk elderly use more free time so that the sense of loneliness and dependence on families is reduced.